Clinical outcomes and echocardiographic characteristics between African American and Caucasian patients with acute pulmonary embolism. (October 2022) - Cires-Drouet, Rafael S; Sama, Jacob; Han, Paul; Jones, Kevin; Haase, Daniel; Miller, Taylor; Toursavadkohi, Shahab; Nagarsheth, Khanjan; Alston, Lateaqua; Smedley, Angela; Shanholtz, Carl; Mayorga-Carlin, Minerva; et al.
Background: Despite socioeconomic disparities, no association between clinical presentation and poor outcomes explains a higher mortality in African Americans with pulmonary embolism (PE). The objective is to identify the co-morbidities and echocardiographic characteristics associated with increased mortality in African American patients. Methods: This is a cross-sectional study of Caucasian or African American patients with PE diagnosed between October 2015 and December 2017 at University of Maryland Medical Center. The outcomes were in-hospital death, length of stay, and bleeding. Results: There were 303 African Americans and 343 Caucasians. Caucasians were older ( p = 0.007), males ( p = 0.01) with history of coronary artery revascularization (CABG ( p = 0.001), coronary stents ( p = 0.001)), trauma ( p = 0.007), and/or recent surgeries ( p = 0.0001). African Americans exhibited higher rates of diabetes ( p = 0.01), chronic kidney disease ( p = 0.0005), and smoking ( p = 0.04). Severity of PE was similar between groups and there was no difference in clot burden size. African Americans had more right ventricular strain on Computer Tomography ( p = 0.001) and echocardiogram ( p = 0.004); also, underfilled left ventricles ( p = 0.02) and higher right ventricular systolic pressures ( p = 0.001). There was no difference in hospital mortality (7.1% vs. 7.9%, p = 0.71), length of stay (13.1 ± 16.7 vs 12.8 ± 14.9, p = 0.80) and bleeding (9.0% vs.8.3%. p = 0.72). Mortality was higher in African Americans who received advanced therapies (3.8% vs. 18.8%, p = 0.02). The risk of death increased with age (OR 1.04; 95%CI 1.020–1.073) and with advanced therapies (OR 2.43; 95%CI 1.029–5.769). Conclusions: Differences in co-morbidities, radiologic findings, and echocardiographic characteristics that may contribute to higher mortality in African American patients, specifically those receiving advanced therapies.